Far-field dynamic behavior of a half-space under an inertial strip foundation subjected to a time-harmonic force - M. Dehestani; N. R. Malidarreh; A. J. Choobbasti; A. Vafai (Latin American Journal of Solids and Structures)
Recent research works demonstrated that the interaction between the loads and the carrying structure's boundary which is related to the inertia of the load is an influential factor on the dynamic response of the structure. Although effects of the inertia in moving loads were considered in many works, very few papers can be found on the inertial effects of the stationary loads on structures. In this paper, an elastodynamic formulation was employed to investigate the dynamic response of a homogeneous isotropic elastic half-space under an inertial strip foundation subjected to a time-harmonic force. Fourier integral transformation was used to solve the system of Poisson-type partial differential equation considering the boundary conditions and the inertial effects. Steepest descent method was employed to obtain the approximate far-field displacements and stresses. A numerical example is presented to illustrate the methodology and typical results.